[Clinical practice guideline for the prevention and management of acute kidney injury in the Social Security of Health of Peru (EsSalud)] - Fernández Burga, Antonio Manuel (2024)
Introduction: This article summarizes the clinical practice guideline (CPG) for the prevention and management of acute kidney injury in the Social Security of Peru (EsSalud). Objective: Provide clinical recommendations based on evidence for the prevention and management of acute kidney injury in EsSalud. Methods: A guideline development group (GEG) was formed that included medical specialists and methodologists. The GEG formulated 6 clinical questions to be answered by this CPG. Systematic searches of systematic reviews and -when considered relevant- primary studies were carried out in PubMed during 2022. Evidence was selected to answer each of the clinical questions posed. The certainty of the evidence was assessed using the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) methodology. In regular work meetings, the GEG used the GRADE methodology to review the evidence and formulate the recommendations, the points of good clinical practice, and the corresponding flowcharts. Finally, the CPG was approved with Resolution No. 099-IETSI-ESSALUD-2022. Results: This CPG addressed 6 clinical questions on prevention, diagnosis and management (fluid therapy). Based on these questions, 5 recommendations (3 strong and 2 conditional), 2 BPCs, and 2 flowcharts were formulated. Conclusion: This article summarizes the methodology and evidence-based conclusions of the CPG for the prevention and management of acute kidney injury in EsSalud.